By My Absolute Royal Authority : Justice and the Castilian Commonwealth at the Beginning of the First Global Age - Owens, J. B. (John B.), 1944- (Book collections on Project MUSE., 2005)
"By My Absolute Royal Authority": Justice and the Castilian Commonwealth at the Beginning of the First Global Age is a study of judicial administration. From the fifteenth century to the seventeenth, the kingdom of Castile experienced a remarkable prolife.